MAKSIMALISASI LABA USAHA: PERSPEKTIF KONVENSIONAL DAN ISLAM - MUHAMAD MUHAMAD (At-Taradhi Jurnal Studi Ekonomi, 2013)
One goal of business is profit-seeking activities. Profit can be a driving force forentrepreneurs to do business. But there are differences between the conventional economic systemwith an Islamic economic system in view of profit. The view on the issue of income of both theeconomic system is dependent on the approach used. Economic theory conventional - in this case -typically uses approach to impersonal in relation with the problem of distribution. This approach ismainly based on market forces, as stipulated by the competition to become a division of 'fair'products for the factors of production. Part workers typically fall within the production costs, so itcan reduce part of workers. In Islam, the positioning of income, profit maximization rationalbehavior in essentially conditioned by three factors: (1) Islam's view of the business, (2) theprotection of consumers, and (3) revenue sharing among the factors that support production.